Association between polycystic ovarian syndrome and endometrial, ovarian, and breast cancer: A population-based cohort study in Taiwan. Issue 39 (September 2018) - Ding, Dah-Ching; Chen, Weishan; Wang, Jen-Hung; Lin, Shinn-Zong
Abstract : Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder among the women of reproductive age. We conducted a nationwide population-based retrospective cohort study to analyze the association between PCOS and the subsequent development of gynecological cancers, namely endometrial, breast, and ovarian cancer. For this population-based cohort study, we used the Taiwan National Health Insurance Research Database, which contains information on approximately 24.7 million insured individuals. The cohort included women who had received a diagnosis of PCOS between 1998 and 2013. An age-matched systematic random-sampling method with a ratio of 1:4 was used for patient selection for the non-PCOS reference cohort. Multivariate Cox proportional hazard regression analysis was used to determine the effects of PCOS on the risks of gynecologic and breast cancer. The data are presented as hazard ratios (HRs) with 95% confidence intervals (CIs). The PCOS cohort consisted of 8155 patients with PCOS, and the comparison cohort consisted of 32, 620 matched patients without PCOS. The incidence of endometrial cancer was 226 and 15 per 100, 000 person-years in the PCOS and comparison groups, respectively. A statistically significant higher risk of endometrial cancer was found in the PCOS cohort (adjusted HR [aHR] = 17.7, 95% CI = 4.9–64.2) than in the comparison cohort. However, no association was observed between PCOS and ovarian (aHR = 1.64, 95% CI: 0.63–4.27) or breast cancer (aHR = 0.98, 95% CI: 0.58–1.65). The results of this large population-based cohort study supported the premise that women with PCOS might have an increased risk of endometrial cancer, but no association between PCOS and the risks of ovarian and breast cancer was found.